Commissioning of projects agricultural transformation building - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
Senator Abiola Ajimobi, Governor of Oyo State Commissions the Agricultural Transformation Building and the Senator Abiola Ajimobi Ring Road, at IITA, Ibadan on May the 25th, 2019.